From the social life of special villages of Uzbekistan - Khudoyorov, Noyibjon (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
The article covers the issues of production activities of special resettlers in labor settlements established in Uzbekistan on the basis of primary sources and special literature